Interleukin-11 drives human and mouse alcohol-related liver disease. Issue 1 (1st April 2022) - Effenberger, Maria; Widjaja, Anissa A; Grabherr, Felix; Schaefer, Benedikt; Grander, Christoph; Mayr, Lisa; Schwaerzler, Julian; Enrich, Barbara; Moser, Patrizia; Fink, Julia; Pedrini, Alisa; Jaschke, Nikolai; et al.
Abstract : Objective: Alcoholic hepatitis (AH) reflects acute exacerbation of alcoholic liver disease (ALD) and is a growing healthcare burden worldwide. Interleukin-11 (IL-11) is a profibrotic, proinflammatory cytokine with increasingly recognised toxicities in parenchymal and epithelial cells. We explored IL-11 serum levels and their prognostic value in patients suffering from AH and cirrhosis of various aetiology and experimental ALD. Design: IL-11 serum concentration and tissue expression was determined in a cohort comprising 50 patients with AH, 110 patients with cirrhosis and 19 healthy volunteers. Findings were replicated in an independent patient cohort (n=186). Primary human hepatocytes exposed to ethanol were studied in vitro. Ethanol-fed wildtype mice were treated with a neutralising murine IL-11 receptor-antibody (anti-IL11RA) and examined for severity signs and markers of ALD. Results: IL-11 serum concentration and hepatic expression increased with severity of liver disease, mostly pronounced in AH. In a multivariate Cox-regression, a serum level above 6.4 pg/mL was a model of end-stage liver disease independent risk factor for transplant-free survival in patients with compensated and decompensated cirrhosis. In mice, severity of alcohol-induced liver inflammation correlated with enhanced hepatic IL-11 and IL11RA expression. In vitro and in vivo, anti-IL11RA reduced pathogenic signalling pathways (extracellular signal-regulated kinases, c-Jun N-terminal kinase, NADPH oxidase 4) and protected hepatocytes and murine livers from ethanol-induced inflammation and injury. Conclusion: Pathogenic IL-11 signalling in hepatocytes plays a crucial role in the pathogenesis of ALD and could serve as an independent prognostic factor for transplant-free survival. Blocking IL-11 signalling might be a therapeutic option in human ALD, particularly AH.